JUSTIFICATION OF STRATEGIC DIRECTIONS FOR INCREASING THE EFFICIENCY OF STATE FINANCIAL MANAGEMENT OF THE REGION - Chernov, Yevhen; Kuznyetsov, Oleksandr; Luzhna, Anastasiia (Socio-economic relations in the digital society, 2023)
The article substantiates the strategic directions of increasing the efficiency of state financial management of the region, proposes an economic-mathematical model for assessing the optimal scale of tax-budgetary decentralization in the conditions of interregional differentiation. The authors emphasize that the urgency of solving the problems of state financial management of the region is due to the impossibility at this stage of creating a certain universal model of regional development. This is primarily related to the unfinished process of forming a comprehensive assessment of the territorial level of development, analysis of socio-economic differentiation and typification of regions, use of state and regional financial policy tools. It is noted that the finances of the region, as the main tool for the implementation of the state socio-economic policy, are designed to promote the development of production, the growth of employment of the population, the attraction of investments in the economy, etc.Three options for the distribution of tax powers between the state and the regions were considered: 1) all tax powers belong to the regions, which independently determine the level of the tax burden and the volume of production of public goods; 2) all tax powers belong to the centre, which determines the level of the tax burden and distributes the received tax revenues between the regions, thus influencing the volume of production of public goods in each of the regions; 3) the distribution of tax powers between the centre and the regions, for which the volume of production of public goods in each of the regions depends both on the tax and budget policy of the centre and on the tax policy of each of the regions. Based on the application of economic-mathematical modelling methods, a conclusion was made about the dependence of the optimal level of decentralization on the level of interregional economic differentiation.Two groups of problems have been singled out, which directly affect the financial management of the region and the consideration of which requires the application of different methodological approaches and methods of state administration: external problems that do not depend on specific regions, are common to all regions of Ukraine, but affect each of them differently them; internal problems that were formed under the influence of internal factors of socio-economic development, which determine the characteristics of each specific region.The key factors of success for a specific region have been determined, provided that certain instruments of state regulation are applied.
Keywords: public administration; regionalization; regional finances; decentralization; socio-economic development; fiscal and budgetary policy; fiscal powers; budgetary transfers